Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s11547-008-0314-1
|View full text |Cite
|
Sign up to set email alerts
|

Cementoplasty in the management of painful extraspinal bone metastases: our experience

Abstract: In our experience, cementoplasty alone for small lesions or combined with RF ablation in larger lesions is an effective and safe therapy in the palliative management of painful extraspinal bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…A retrospective study reported 3 % deep vein thrombosis within 3 months after surgery, and a death rate of 1 % during surgery, 9 % during the hospital stay and 13.9 % within 3 months after surgery [15]. Although percutaneous cementoplasty has been used as an alternative for stabilization of impending pathological fractures of the long bones, several groups have reported that despite satisfactory pain relief after the procedure, pathological fractures were the most common delayed adverse event following PLBC [3,[5][6][7]. The main reason is that injecting cement directly into osteolytic lesions cannot provide adequate mechanical stability for long bones, which is considered resistant to compressive forces, but less so to torsional forces [16][17][18], and long bones treated by PLBC are more subject to torsional forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study reported 3 % deep vein thrombosis within 3 months after surgery, and a death rate of 1 % during surgery, 9 % during the hospital stay and 13.9 % within 3 months after surgery [15]. Although percutaneous cementoplasty has been used as an alternative for stabilization of impending pathological fractures of the long bones, several groups have reported that despite satisfactory pain relief after the procedure, pathological fractures were the most common delayed adverse event following PLBC [3,[5][6][7]. The main reason is that injecting cement directly into osteolytic lesions cannot provide adequate mechanical stability for long bones, which is considered resistant to compressive forces, but less so to torsional forces [16][17][18], and long bones treated by PLBC are more subject to torsional forces.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use for long bone osteolytic metastases is controversial. Several reports have indicated that despite satisfying pain relief after the procedure, there was a risk of fracture due to insufficient mechanical stability [3,[5][6][7]. To overcome these disadvantages, we adopted an innovative method -PLBC combined with embedding a cement-filled catheter in the long bone medullary canal (ECFC) -to minimize the risk of fracture and to improve mechanical stability [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cementoplasty has produced some promising results used either alone or in conjunction with radiofrequency ablation in the treatment of symptomatic extra-spinal metastatic lesions. 12 The main purpose of embolization is to achieve thrombus formation and occlusion by administrating embolizing materials through a selective catheter placed in an arterial or venous vessel. Embolizing agents must be nontoxic, sterile, radiopaque, and easy to prepare or obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Antalgic medical therapy, often based on opiates, is frequently not sufficient and has well-known heavy side effects. Several studies have demonstrated the feasibility, efficacy, and safety of PV in the treatment of vertebral localizations of MM, but up to date, to our knowledge, even though the use of percutaneous osteoplasty (a de facto technical extension of PV) in the case of extraspinal malignant lesions has been reported in literature, its potential role has been assessed in studies involving case series which included a small number of MM cases [5,[13][14][15]. The main result of our study is a significant short-and long-term drop in VAS pain scores with a consequent major reduction of analgesic use.…”
Section: Discussionmentioning
confidence: 99%